(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The theme of the scourge of unemployment in human societies is not the result of hours whether at the international level in general or on the level of Iraq in particular. Since many researchers wrote and discussed this subject, and they reached to satisfactory results. The reason for interest in this subject is because it affects human life because of their economic damage as does the low-income or not and therefore lower spending on health leading to a decline in production in the event of his return to work. As well as damage to social and psychological sense is an unemployed frustration and lack of self-confidence and sense of belonging to their homeland over the size of the offences and family and social disintegration . Therefore, the objective of the research was to identify the reality of unemployment in the governorates of Iraq and know the differences in unemployment rates between the governorates and size between work and assess trends and the expectations for in 2012 of the workforce in the governorates of Iraq Research results showed that there was an increase in the total unemployment rate seems clear from in 2005 (33.37%) even in 2006 and (38.1%), and this refers to aggravate the unemployment crisis and the large unemployed to work and entrants to the labor market. Highest rate and the contribution of labor power to Iraqi population in the governorates are located in the governorates of Babel and it by percentage (%17) from the population of Babel which is a reasonable percentage compared to the number of population, while the minimum rate of contribution in the governorates of Diyala was rate it (%7) of the population of Diyala. As for the volume of labor power total in 2000 was about (10600713) employed and unemployed. While the expected in 2012 about (14958474) employed and unemployed. Show that there is an annual increase in the volume of unemployment in governorates Iraq amount it (59905) unemployed work and able to work, looking for work and no finds. Unemployment in the southern and northern governorates is compulsory unemployment, because it could at least partially solve from through government One of the most important research proposals is that the government of its responsibility towards the unemployed youth to work especially graduates of them through the creation and implementation of investment projects in different economic sectors in the governorates which (relatively safe) compared with the Central governorates And the work to develop the skills of the unemployed through training sessions in the governorates of Iraq and of various specialties with the Ministries of Youth and Sports and Labor and Social Affairs.